2012
DOI: 10.1055/s-0032-1327003
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging of the Shoulder: First Dislocation versus Chronic Instability

Abstract: Traumatic dislocation of the shoulder is a frequent injury in the young and active population. An acute shoulder dislocation often denotes a onetime traumatic episode, whereas chronic shoulder instability indicates multiple recurrent dislocations. Imaging, in particular MRI, is a useful tool that can accurately demonstrate the typical soft tissue and osseous markers of shoulder dislocation. However, the ability to differentiate between first time versus recurrent dislocation based on imaging remains in questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 91 publications
(133 reference statements)
0
6
0
Order By: Relevance
“…[1,2] Various studies have found that patient's age, gender and athletic involvement were reliable predictors for recurrence with age during initial dislocation appearing to be the most common predisposing factor. [3] Rowe et al showed that the rate of recurrence of shoulder dislocation got decreased as patients got old with 83% of patients below age 20, 63% between 20 and 40, and 16% of patients older than 40 likely to have recurrent dislocation. [4] Teslaa et al found that there was a 71% recurrence rate in patients less than 18 years of age at 5-year followup period when compared with the overall group of 16-to 39-year-old patients who demonstrated a recurrence rate of about 55%.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] Various studies have found that patient's age, gender and athletic involvement were reliable predictors for recurrence with age during initial dislocation appearing to be the most common predisposing factor. [3] Rowe et al showed that the rate of recurrence of shoulder dislocation got decreased as patients got old with 83% of patients below age 20, 63% between 20 and 40, and 16% of patients older than 40 likely to have recurrent dislocation. [4] Teslaa et al found that there was a 71% recurrence rate in patients less than 18 years of age at 5-year followup period when compared with the overall group of 16-to 39-year-old patients who demonstrated a recurrence rate of about 55%.…”
Section: Discussionmentioning
confidence: 99%
“…While CT scans are the gold standard for assessing bone loss, MRI has been shown to be accurate and reliable for the measurement of GBL. 14,29 In addition, MRI studies have been used recently to define posterior critical bone loss. 1 Given that the present study relied on proportions of bone loss, rather than absolute bone loss, the use of both imaging modalities is not likely to influence the results of the study.…”
Section: Limitationsmentioning
confidence: 99%
“…The Hill-Sachs lesion should not be confused posterosuperiorly with the bare area at the junction between the footprint of the infraspinatus and the articular cartilage nor posteroinferiorly with the flattened area of the normal humeral neck. On axial images, the Hill-Sachs lesion is typically found at the level of the coracoid process, whereas the neck is far below this level [ 1 35 68 72 77 80 84 85 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 107 ].…”
Section: What Shouldn’t We Miss In Patients With Recurrent Anterior Dmentioning
confidence: 99%
“…These reversed lesions have the same imaging characteristics as their anterior homonyms. Anteriorly, a reversed Hill-Sachs lesion can be found medial to the lesser tuberosity [ 9 30 46 67 72 74 95 108 109 110 111 112 113 114 115 116 ].…”
Section: What Shouldn’t We Miss In Patients With Recurrent Anterior Dmentioning
confidence: 99%
See 1 more Smart Citation